2022
DOI: 10.1101/2022.09.20.508560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of an Agrobacterium-delivered codon-optimized CRISPR/Cas9 system for chickpea genome editing

Abstract: Chickpea is considered recalcitrant to in vitro tissue culture. The Clustered, Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/Cas9) based genome editing in chickpea can remove the bottleneck of limited genetic variation in this cash crop rich in nutrients and protein. However, the generation of stable mutant lines using CRISPR/Cas9 requires efficient and highly reproducible transformation approaches. We modified a binary vector pPZP200 by introducing a codon-optimized Cas9 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Several previously published studies indicated that CRISPR/Cas9-mediated PDS gene-edited mutants were photosensitive and failed to survive. 23 , 32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previously published studies indicated that CRISPR/Cas9-mediated PDS gene-edited mutants were photosensitive and failed to survive. 23 , 32 …”
Section: Resultsmentioning
confidence: 99%
“… 26 It also allows for simple screening of mutant lines. 27 , 28 Recent studies have shown the establishment of efficient genome editing using the PDS gene through the CRISPR/Cas9 system in several crops, including potato, 24 pea, 29 papaya, 30 coffee, 31 chickpea, 32 hop, 23 onion 25 and squash. 33 Nevertheless, the development of a biolistic-mediated CRISPR/Cas9-reagent delivery system using the PDS gene in chilli pepper has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…8C, D, and F). A handful of reports are available that show editing experiments in chickpeas (Gupta et al 2023). This protocol will facilitate researchers to undertake genome editing in chickpeas.…”
Section: Discussionmentioning
confidence: 99%